Monolithically Integrated O-Band Coherent ROSA Featuring 2D Grating Couplers for Self-Homodyne Intra Data Center Links - Pascal M. Seiler; Galina Georgieva; Anna Peczek; Matthieu Oberon; Christian Mai; Stefan Lischke; Andrea Malignaggi; Lars Zimmermann (IEEE Photonics Journal)
In this work, we present an O-band dual-polarization coherent receiver optical sub-assembly (cROSA), monolithically integrated in a 0.25 $μ$ m BiCMOS technology. The receiver features 248 nm deep ultra violet compatible 2-dimensional grating couplers (2D-GRCs), and an adaptive polarization controller, suitable for mitigation of local oscillator induced power fading in self-homodyne transmission systems. The cROSA is evaluated in system experiments at 64 GBd quadrature-phase shift-keying. Experimental results are related to grating coupler induced polarization crosstalk through Monte-Carlo simulations. Second generation 2D-GRCs are proposed.